Exploring employers' perceptions on public universities' quality and graduate employability in Malaysia - Almasri, Amal Ahmad; Ali, Noor Azman; Jantan, Amer Hamzah (Inderscience Publishers, 2024)
This study was conducted to explore the employers’ perceptions of the relationship between the quality of public universities and graduate employability. This study adopted a qualitative research design by using a semi- structural interview with ten employers. The findings indicate the determinants of university quality, including university outcomes, reputation, academic program and curriculum, infrastructure and support facilities, academic staff, and training as influential factors on graduate employability. In addition, employers commented that graduate employability could be influenced by top management commitment, especially when they seek to communicate with stakeholders to determine the workplace’s needs to improve their graduate employability. Whilst, employers consider admission requirements of public universities are not based on academic excellence, but on the quantity of students. Therefore, this study recommends that the higher authorities in public universities and employers need to strengthen the associations between them and activate partnerships for all parties’ benefit. As well, public universities need to pay more attention to the determinants of quality, which contribute to enhancing graduate employability.